2017
DOI: 10.1002/bjs.10603
|View full text |Cite
|
Sign up to set email alerts
|

Trends in indications, complications and outcomes for venous resection during pancreatoduodenectomy

Abstract: Despite an initial improvement in severe complications for venous resection during pancreatoduodenectomy, this was not maintained over time. Every fourth patient with venous resection needed relaparotomy, most frequently for bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 43 publications
1
36
2
Order By: Relevance
“…An increasing number of patients with locally advanced disease or borderline resectable tumors are offered surgery by means of concomitant vascular resection of the portal vein or superior mesenteric vein. 1,2 In the presence of arterial involvement, neo-adjuvant chemotherapy is advocated to improve the possibility of resection. 3 For jaundiced patients with resectable pancreatic cancer, surgery rather than preoperative biliary drainage is advocated to relieve biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of patients with locally advanced disease or borderline resectable tumors are offered surgery by means of concomitant vascular resection of the portal vein or superior mesenteric vein. 1,2 In the presence of arterial involvement, neo-adjuvant chemotherapy is advocated to improve the possibility of resection. 3 For jaundiced patients with resectable pancreatic cancer, surgery rather than preoperative biliary drainage is advocated to relieve biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Resection of the superior mesenteric vein/portal vein is routine in some centres, where patient survival is equivalent to that of patients who undergo resection with no vascular involvement 5 . Ravikumar and colleagues 5 and Kleive et al 6 , however, report a need for relaparotomy among between 7 and 24 per cent of patients in this group. There is little understanding of the institutional or geographical variation in this practice, which is largely influenced by local experience, centre volume and dogma.…”
mentioning
confidence: 82%
“…Resection of the superior mesenteric vein/portal vein is routine in some centres, where patient survival is equivalent to that of patients who undergo resection with no vascular involvement. Ravikumar and colleagues and Kleive et al ,. however, report a need for relaparotomy among between 7 and 24 per cent of patients in this group.…”
mentioning
confidence: 99%
“…However, more recent data have shown that a venous resection during pancreatic resections for PDAC is associated with increased rates of complications (41)(42)(43)(44). A posterior or a mesenteric approach appears to facilitate a venous resection and reconstruction during pancreatico-duodenectomies for PDAC (7,27,45,46).…”
Section: Borderline Resectable Pdacmentioning
confidence: 99%